Detection of a relationship between Osteoporosis and Helicobacter pylori infection and Vitamin D3 deficiency - M. Al-Omari, Raad; M. Al-Rawi, Amera (YCAB Publisher, 2025)
Background:Helicobacter pylori (H. pylori) is a gram-negative bacterium that has been implicated in influencing bone metabolism and potentially promoting the development and incidence of osteoporosis (OP). OP is characterized by low bone mineral density, which is associated with an increased risk of fractures. Emerging evidence suggests that H. pylori positivity rates appear to be higher among individuals with vitamin D deficiency. Vitamin D3 plays a crucial role in maintaining bone health, and its deficiency is often linked to compromised bone strength and density. Objectives:This study aims to investigate the relationship between H. pylori infection and osteoporosis, the association between H. pylori infection and vitamin D3 levels, and the correlation between osteoporosis and vitamin D3 levels. Methods:A total of 120 samples were collected and divided into two groups: 60 samples from osteoporosis patients (30 fecal samples and 30 blood samples) and 60 samples from healthy individuals (30 fecal samples and 30 blood samples). Fecal samples were used to detect H. pylori antigen (Ag), while blood samples were analyzed for H. pylori antibody (Ab) and vitamin D3 levels. Results:Among osteoporosis patients, 75% tested positive for H. pylori Ag, while 25% were negative. In the healthy group, 20% were positive and 80% were negative for H. pylori Ag. Furthermore, 93.33% of osteoporosis patients who were positive for H. pylori Ag had vitamin D3 levels ≤29 ng/ml, and only 6.66% had vitamin D3 levels ≥30 ng/ml. Among the healthy individuals positive for H. pylori Ag, 100% had vitamin D3 levels ≤29 ng/ml. In the healthy group negative for H. pylori Ag, 53.33% had vitamin D3 levels ≤29 ng/ml, while 46.66% had levels ≥30 ng/ml. Additionally, 55% of osteoporosis patients had severe vitamin D3 deficiency (≤20 ng/ml), 35% had moderate deficiency (21–29 ng/ml), and 10% had sufficient levels (≥30 ng/ml). Among healthy individuals, 25% had severe deficiency (≤20 ng/ml), 40% had moderate deficiency (21–29 ng/ml), and 35% had sufficient levels (≥30 ng/ml). Conclusion:The findings of this study indicate a strong association between H. pylori infection and osteoporosis, with a higher prevalence of H. pylori infection observed among osteoporosis patients. Moreover, both H. pylori infection and osteoporosis were associated with lower vitamin D3 levels, highlighting the potential role of H. pylori in contributing to vitamin D3 deficiency and impaired bone health. These results underscore the importance of screening for H. pylori infection and monitoring vitamin D3 levels in patients at risk for osteoporosis. Keywords: H. pyloriinfection; OP; Vitamin D3 level; DEXA; fecal; blood